Ursprungs- och kvalitetsmärkningens betydelse för konsumentens val av krukväxter - Liljedahl, Sara (2010)
This essay has been made on behalf of the co-operative society Mäster Grön, which is selling ornamental plants to retailers in Sweden. The aim of this study has been to find out what added value Mäster Grön gets from their co-branding with the Swedish Seal of quality. The main topic of discussion was; how much value added does this co-branding give to Mäster Gröns pot plants? Are there differences from a customer point of view in value added between a garden center and a retail store? How much weight does the costumer put on the branding when buying a plant? Does the customer know what the values of Mäster Grön and Swedish Seal of quality mean? Two questions of lesser worth were asked to the consumers about what they thought about the protective plastic around the plant, and if they were interested in getting more information about the origin as well as the method of production of the plant. The study was divided into two parts, one in which customers were observed and one where the customers answered a survey. Both these techniques were used in one supermarket and one garden center in Stockholm. During the observation the flow of customers was observed and their actions at one table with three differently branded plants were monitored. In the first section the plant had Swedish Seal of quality and Mäster Grön branding, in the second section the plant was only branded with the Mäster Grön logotype and the plant in the third section did not have any branding at all. After the customer had made its choice from the table, questions were asked about the choices made. The survey consisted of 18 questions and was handed out to 160 customers divided equally among the garden center and the supermarket. In one of the questions consumers were asked to rank the different branded flowers mentioned above in order of most likely purchase to the least likely to be purchased. Other questions asked to the consumers in the survey concerned which values they considered important when purchasing a plant in the store as well as the rate of recognition of Swedish seal of quality and Mäster Grön. Because of too few results in the observation part of the study a reliable result could not be read. However, in the other part of the study, the survey, a more reliable result can be found. The results of the question were the consumer had to rank the flower most likely purchased, most consumers said that they would most likely buy the plant branded with both Mäster Grön and the Swedish Seal of quality, then the plant only branded with Mäster Grön. Consumers answered that they were least likely to buy the plant with no branding at all. About 50 % of the consumers said that they recognize the Mäster Grön logotype. Among them 50 % associated Mäster Grön with ornamental plants and the rest associated it with fruit and vegetables. Two out of three consumers recognized the Swedish Seal of quality. However, solely a handful of the asked knew what its values were. The largest difference between the stores compared show that more consumers from the supermarket recognized the Mäster Grön and the other logotypes showed on the plants compared to the consumers answering the survey in the garden center. Most consumers answering the survey were positive to the plastic around the plants, as well as to getting more information about origin and way of production. The conclusion was that the value added that Mäster Grön and the Swedish Seal of quality gets through their co-branding is good, but with extensive marketing and better exposure they have the potential to regain even more added value.